TRANSFORMATION OF EPIC GENRES: KHAMSA, EPOS, AND THE NOVEL - U. H. Juraqulov (Journals Park Publishing, 2025)
The article provides an extensive discussion of the transformation of epic genres and the poetic interrelation among khamsa, epos, and the novel. In particular, when the poetic connection among these genres is examined through the artistic chronotope, plot, motifs, and the system of images, typological aspects become evident. It is emphasized that a complex study of the typology of khamsa, epos, and novel is of great importance not only for theoretical literary criticism, but also for the development of the methodological foundations of history, sociology, philosophy, and aesthetics.
Keywords: Transformation of epic genres, khamsa, epos, novel, typology, artistic plot, motif, detail and system of images, lover–beloved–rival triad, meeting, separation, reunion motifs.